1991
DOI: 10.1128/aac.35.12.2602
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue penetration of a single 1,000-milligram, intravenous dose of metronidazole for antibiotic prophylaxis of colorectal surgery

Abstract: The levels of metronidazole in serum and tissue penetration of metronidazole were studied after prophylactic administration in 11 patients undergoing elective colorectal surgery. A single dose of 1,000 mg given intravenously was administered before surgery. Adequate drug levels in serum (.MIC for 90% of strains tested [MIC90] for Bacteroides fragilis) were found in all patients throughout the procedure. Mean peak (15-min) and last-determined (24-h) metronidazole levels in serum were 28.8 ± 8 and 4.2 ± 1.7 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…In the present study, the extend of penetration of both compounds was maintained throughout the surgical procedure probably because of the second injection performed after 120 min. This emphasizes the need for repeated injections of drugs with shorter half-lives (4,8,13,18,19). Had this second injection not been performed, decreased concentrations of both compounds would probably have been measured in fatty tissues, with an increased risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the extend of penetration of both compounds was maintained throughout the surgical procedure probably because of the second injection performed after 120 min. This emphasizes the need for repeated injections of drugs with shorter half-lives (4,8,13,18,19). Had this second injection not been performed, decreased concentrations of both compounds would probably have been measured in fatty tissues, with an increased risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…It seems clear that during a surgical procedure, adequate antibiotic concentrations should be achieved at all sites of potential infection. Also, antibiotic activity should be maintained throughout the procedure, from incision to closure (4,6,8,13,14,18,19).…”
mentioning
confidence: 99%
“…It is distributed widely and reaches 42 to 76% of plasma concentrations in colonic mucosa (9,13). Metronidazole is extensively metabolized by the liver and excreted predominantly in feces, with only 12% excreted unchanged in urine (12).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the pharmacokinetics of intravenous metronidazole after single-dose administration to patients (5,19,28,32,34) and healthy volunteers (4,15,17). Pharmacokinetic parameters derived from plasma metronidazole concentrations after multiple doses in our healthy volunteer study were similar to those reported after single-intravenous-dose administration of 500 mg by Loft et al (17), 1,000 mg by Lau et al (15), and 1,500 mg by Bergan et al (4) to healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%